Peritumoral Edema/Tumor Volume Ratio: A Strong Survival Predictor for Posterior Fossa Metastases. Issue 1 (11th June 2018) - Calluaud, Gauthier; Terrier, Louis-Marie; Mathon, Bertrand; Destrieux, Christophe; Velut, Stéphane; François, Patrick; Zemmoura, Ilyess; Amelot, Aymeric
Abstract: BACKGROUND: Twenty percent of all brain metastases (BM) occur in the posterior fossa (PF). Radiotherapy sometimes associated with surgical resection remains the therapeutic option, while Karnovsky performance status and graded prognostic assessment (GPA) are the best preoperative survival prognostic factors. OBJECTIVE: To explore the prognostic role of peritumoral brain edema in the PF, which has never been explored though its role in supratentorial BM has been debated. METHODS: A total of 120 patients diagnosed with PF metastasis who underwent surgical resection were included retrospectively in this analysis. Clinical data were retrieved from electronic patient medical files. The tumor volumes and their associated edema were calculated via manual delineation; subsequently the edema/tumor volume ratio was determined. RESULTS: In multivariate analysis with Cox multivariate proportional hazard model, the edema to tumor volumes ratio (hazard ratio [HR]: 1.727, 95% confidence interval [CI] 1.427-2.083; P < .0001) was identified as a new strong independent prognosis factor on overall survival (OS) whereas edema volume alone was not ( P = .469). Moreover, BM complete resection (HR: 0.447, 95% CI 0.277-0.719; P < .001), low (0-1) World Health Organization status at diagnosis (HR: 2.109, 95% CI 1.481-3.015; P < .0001), high GPA class at diagnosis (HR: 1.77, 95% CI 0.9-2.9; P < .04), and postoperative brain irradiation (HR: 2.019, 95% CI 1.213-3.361; P < .007] were all confirmed as independent predictive factors for survival. CONCLUSION: The edema/tumor ratio appears to greatly influence OS in patients suffering from PF metastases unlike the extent of edema alone. This easily determined as well as strong prognostic factor could be used as an interesting tool in clinical practice to help the management of these patients.